Selecting experimental super sweet corn hybrids based on selection index - Zaluski,Welton Luiz (2021)
ABSTRACT Super sweet corn hybrids shall present production and quality traits in order to meet farmer’s, industry and consumer’s expectations. The aim of this study was to select experimental super sweet corn hybrids based on the Z index (I Z ). We evaluated 64 experimental hybrids from crosses between inbred lines of different groups along with two check hybrids. The experiments were carried out in Guarapuava-PR in two sowing seasons in 2016. The evaluated traits were male flowering, ear length, ear diameter, soluble solids content, husked ear yield, unhusked ear yield, and grain yield. The traits which most contributed to the Z index were related to ear and grain yields and soluble solids content. The first sowing season was the most favorable for the expression of yield related traits. The experimental hybrid D3-30 x D5-46 showed high performance in both sowing seasons and the hybrid D2-17 x D5-46 stood out in the second sowing season, being both promising, showing high productivity and quality of ear, considering the Z index.